Utilization of Tofu Liquid Waste with Ceramic-Based Microbial Fuel Cell (MFC) Technology - Wafi, Moh. Abduh; Ahmad, Mutiara Garnet; Misto, Misto; Cahyono, Bowo Eko; Mulyono, Tri; Mutmainnah, Mutmainnah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
The application of ceramic-based Microbial Fuel Cells (MFCs) for the treatment of tofu liquid waste presents a promising and environmentally sustainable approach. The purpose of this study was to determine the effect of adding variations in substrate concentration and to determine the effect of variations in the surface area of the electrode (anode and cathode), resulting in a maximum power density value for a period of 13 days of measurement. The initial step is measuring the voltage and current with the substrate concentration without a dilution process, then the concentration variations are carried out by dilution 10 times, 8 times, 5 times, 4 times, and 2 times on ceramics with a diameter of 8 cm. The second step is measuring the voltage and current by varying the surface area of the electrodes (cathode and anode). The results of the measurements obtained that the maximum power density value obtained was 188.23 mW/m2 without a dilution process, namely with a concentration of 3640 ppm for the third day. Meanwhile, the results of the measurement of the variation of the electrode surface area obtained a maximum power density value of 205.88 mW/m2 on the electrode surface area of 3.57 m2 for the third day. The more surface area of the electrode given at the time of measurement, the more bacteria contact the electrode, causing the resulting power density value to be even greater.